Perbandingan Kinerja Keuangan Rumah Sakit Umum dan Khusus : (Studi Kasus Periode Sebelum dan Saat Pandemi Covid-19) - Reny Marliadi; Noor’adia Noor’adia; Rahmat Rama Maulana; Liana Fitriani; Andri Nur Rahman (AKUNTANSI 45, 2024)
Hospitals as business entity, aside from fulfilling its social mission as public services institution, should perform financial management to accommodate the user’s need. This research carries out the financial ratios analysis and to compare financial performance between a general hospital and specialized hospital with quantitative approach and descriptive technique, in which both hospitals aren’t referral hospitals for Covid-19. This research also aims to analyze the comparation of the trend on financial ratios analysis before Covid-19 (2018-2019) and during Covid-19 (2020-2022). The results showed that the general hospital’s liquidity increased before Covid-19 to during Covid-19, while the specialized hospital liquidity experienced a fluctuating trend. Fortunately, both general hospitals and specialized hospitals has its activity ratios tend to increase during period 2018-2022. Solvability ratios analysis conclude that before Covid-19, both general hospitals and specialized hospital’s ability of managing their debt to get assets influenced by BPJS service debt, and during Covid-19 influenced by the regulation of budget refocusing policy. Meanwhile, this research found that both hospitals haven’t yet optimize their ability to generate surplus, moreover their deficit from before Covid-19 to during Covid-19 increased.